Leadership selection in an unlimited three-echelon supply chain - Jia, Peng; Mahdiraji, Hannan Amoozad; Govindan, Kannan; Meidutė, Ieva (Journal of Business Economics and Management, 2013)
Supply chain (SC) management aims to increase the overall profit through improvement of various activities and components. Many contradictions between parts and different levels of a SC have been identified in order to achieve overall objectives. Such shortfalls may result in decreased strength and competitiveness of the SC. This paper considers the main conflicts related to inventory, pricing and marketing costs in an unlimited three-echelon supply chain. Aimed at avoiding a profit decrease, the research focuses on finding an equilibrium between inventory, pricing and marketing cost of an unlimited three-echelon SC. On each level, the best leadership option with the greatest payoff is sought for between K retailer, M manufacturer and S supplier. According to Stackelberg non-cooperative game theory, each SC level can become a decision-making leader depending on the available negotiating power. Consequently, three leadership types are modelled on each level and the total SC profit is calculated and compared to ascertain the best option. The authors of the article found that transfer of leadership from a retailer to supplier results in reduction of the total profit. In addition, the research focused on the main effects of parameters used in leadership models. Finally, validation of the proposed model was examined by simulation and Arena software, which indicated that models based on a game theory were performed accurately.